An Educational Resource Based on Water and Health as a Teaching Aid in French Primary Schools Part I: Identification of Needs and Content - Chantal Savanovitch; Marie-Pierre S (MDPI AG, 2013)
It is a commonplace that water is essential for life, but to what extent is the general public, and children in particular, aware of how water affects health? The aim of this review was to consider the relationship between water and health under three main headings: the importance of hydration for children, dietary intake of water, and water as an essential factor in hygiene contributing to good health. The literature was reviewed to provide a rationale for the implementation of teaching about water and health in French primary schools under three main areas: (i) the importance of hydration for school children and water promotion in primary schools; (ii) the problem of overweight/obesity and the need to adopt healthy drinking habits as defined in French nutritional policy; (iii) the survey of the quality of drinking water in France and its relationship with good hygiene practices. There are currently few educational resources in France on water and health that teachers can use in the classroom. This review gives reasons why a "Water and Health" learning resource is a useful tool and shows how it can be developed within the constraints imposed by the school syllabus and in accordance with French nutritional and environmental policy.